The Use of Combination of Clarithromycin -Nano Oxide Nanoparticles to Doping PVC to Protect it from Photodegradation - A. Husain, Amani (Al-Nahrain Journal of Science, 2022)
Films of polyvinyl chloride with oxide nanoparticles (MgO, NiO, TiO2, and ZnO) and clarithromycin were prepared. Oxide nanoparticles were used in low concentrations (0.01% by weight) along with clarithromycin. The analysis of oxide nanoparticles and clarithromycin as UV blockers for PVC photodegradation investigations into weight loss, surface morphology, and IR changes, revealed that titanium oxide, especially, protects PVC from harmful ultraviolet light.